Centrosymmetric and chiral porous thorium organic frameworks exhibiting uncommon thorium coordination environments. Issue 48 (13th November 2015) - Li, Yuxiang; Weng, Zhehui; Wang, Yanlong; Chen, Lanhua; Sheng, Daopeng; Liu, Yunhai; Diwu, Juan; Chai, Zhifang; Albrecht-Schmitt, Thomas E.; Wang, Shuao
Abstract : The solvothermal reaction of thorium nitrate and tris-(4-carboxylphenyl)phosphine oxide in DMF affords a centrosymmetric porous thorium organic framework compound [Th(TPO)(OH)(H2 O)]·8H2 O (1 ). Abstract : The solvothermal reaction of thorium nitrate and tris-(4-carboxylphenyl)phosphine oxide in DMF affords a centrosymmetric porous thorium organic framework compound [Th(TPO)(OH)(H2 O)]·8H2 O (1 ). In contrast, the ionothermal reaction of the same reagents in the ionic liquid 1-butyl-2, 3-dimethylimidazolium chloride results in the formation of a rare example of a chiral and porous thorium organic framework compound, [C9 H17 N2 ][Th(TPO)Cl2 ]·18H2 O (2 ), which is derived solely from achiral starting materials. The geometries of the Th(iv ) centers in compounds1 and2 are both atypical for low valent actinides, which can be best described as a ten-coordinate spherical sphenocorona and an irregular muffin, respectively. A large cavity of 17.5 Å (max. face to face) × 8 Å (min. face to face) with a BET surface area of 623 m 2 g −1 in compound2 is observed. The poor stability indicated by thermal gravimetric analysis and the water-resistance test for compound2 may be due to the unique anisotropic coordination geometry for thorium. Temperature-dependent luminescence studies for both compounds indicate that the trends in the intensity vary as the Th–Th distance and the coordination environments of Th(iv ) centers change.